QUADRUPLE HELIX AS A DEVELOPMENT INDUSTRY MODEL OF BATIK TULIS LASEM REMBANG REGENCY - Muhammad Tahwin; Anik Nurhidayati; Dian Ayu Liana Dewi (STIE Pelita Nusantara Semarang, 2022)
This study aims to formulate the Quadruple Helix model in developing the Lasem Batik Tulis industry. The object of research is the Lasem Batik Industry, Rembang Regency. Methods of data collection used questionnaires and interviews. The sampling technique used purposive sampling. Data analysis used SWOT analysis and the Quadruple Helix concept. The results show that the formulation of the right combination of SWOT matrix strategies as an effort to develop the Batik Tulis Lasem industry is the Strenghts Opportunities (SO) strategy as many as 10 strategies, namely: (1) Implementation of regulations for the preservation of Batik Tulis Lasem, policies and business empowerment of Batik Tulis Lasem, (2) Optimization of studies and research to support product, service and managerial creativity, (3) Improvement and facilitation of batik lover events, (4) Improving the quality of exhibitions for all batik entrepreneurs who already have new names and businesses, (5) Update designs and follow development of modes to compete with other products, (6) Improving the quality of facilities and services, (7) Utilizing loan facilities for business development, (8) Maintaining product quality, (9) Optimizing training and mentoring programs (10) Increasing the role of the Government in strengthening batik cooperatives and clusters. Furthermore, the 10 strategies are described in the Quadruple Helix model scheme for the Development of the Lasem Batik Handicraft Industry.